Весьегонская волчица: [Сборник] / Б. Т. Воробьев - Воробьев Борис Тимофеевич (Библ. сер., 1989)
Экземпляры: ф-7 (ретроконверсия) / Инвентарный номер: 26310 / Цена: 3.00 / Сис.шифр: 28.68 / Авт.знак: В75 / ББК: 28.68